Comparative genomics of Lactobacillus - Kant, Ravi; Blom, Jochen; Palva, Airi; Siezen, Roland J.; de Vos, Willem M. (Microbial biotechnology, 2011)
Summary The genus Lactobacillus includes a diverse group of bacteria consisting of many species that are associated with fermentations of plants, meat or milk. In addition, various lactobacilli are natural inhabitants of the intestinal tract of humans and other animals. Finally, several Lactobacillus strains are marketed as probiotics as their consumption can confer a health benefit to host. Presently, 154 Lactobacillus species are known and a growing fraction of these are subject to draft genome sequencing. However, complete genome sequences are needed to provide a platform for detailed genomic comparisons. Therefore, we selected a total of 20 genomes of various Lactobacillus strains for which complete genomic sequences have been reported. These genomes had sizes varying from 1.8 to 3.3 Mb and other characteristic features, such as G+C content that ranged from 33% to 51%. The Lactobacillus pan genome was found to consist of approximately 14 000 protein‐encoding genes while all 20 genomes shared a total of 383 sets of orthologous genes that defined the Lactobacillus core genome (LCG). Based on advanced phylogeny of the proteins encoded by this LCG, we grouped the 20 strains into three main groups and defined core group genes present in all genomes of a single group, signature group genes shared in all genomes of one group but absent in all other Lactobacillus genomes, and Group‐specific ORFans present in core group genes of one group and absent in all other complete genomes. The latter are of specific value in defining the different groups of genomes. The study provides a platform for present individual comparisons as well as future analysis of new Lactobacillus genomes.